Nationalism and Revolution in Indonesia - Kahin, George McTurnan (Studies on Southeast Asia ;, 2019)
Professor Kahin's classic 1952 study, reprinted for a contemporary audience. An immediate, vibrant portrait of a nation in the age of revolution, featuring interviews with many of the chief players. With new illustrations and a new introduction by Benedict R. O'G. Anderson.